Recanalization Treatment of Acute Ischemic Stroke Caused by Large-Artery Occlusion in the Elderly: A Comparative Analysis of "the Elderly" and "the Very Elderly". (6th October 2021) - Wang, Qi; Zhang, Yi-Qun; Qiu, Han-Cheng; Yao, Yin-Dan; Liu, Ao-Fei; Li, Chen; Jiang, Wei-Jian
Abstract : Objective . To assess whether the effectiveness and safety of recanalization therapy for acute ischemic stroke (AIS) caused by large-artery occlusion (LAO) differ between patients aged 60–79 years and patients aged ≥80 years. Methods . We analyzed prospective data of patients with LAO (≥60 years) who underwent recanalization therapy at the Department of Vascular Neurosurgery, New Era Stroke Care and Research Institute, PLA Rocket Force Characteristic Medical Center, from November 2013 to July 2017. The data were compared between elderly patients (60–79 years) and very elderly patients (≥80 years). The effectiveness of recanalization therapy was evaluated using the 90-day modified Rankin scale (mRS) score, while safety was assessed by the rates of symptomatic intracranial hemorrhage (SICH) and mortality within 30 days. Results . A total of 151 patients with AIS induced by LAO were included in this study. Seventy-three patients (48.3% [73/151]) had an overall favorable outcome (mRS score 0–2) after treatment. A higher proportion of patients in the elderly group showed a favorable outcome compared with the very elderly group (58.6% [34/58] vs. 41.6% [39/93], respectively; P = 0.046 ). The incidence of SICH (12.7% vs. 16.13%, respectively; P = 0.561 ) and mortality (10.3% vs. 7.5%, respectively; P = 0.548 ) within 30 days was not significantly different between the two groups. Conclusion . Recanalization treatment of LAO is more effective in elderly patients compared with very elderly patients, while the safety of recanalization treatment is comparable between these two groups.